(untitled) (Medicine Today, 2024)
Introduction: A prospective observational study was conducted to compare the paramedian incision with midline incision in gastro-intestinal tract perforation. Objectives: To identify better or superior incision which may reduce post operative mortality and morbidity after laparotomy. Materials and Methods: A prospective observational Hospital based study was conducted from January 2009 to June 2009 at department surgery of Shaheed Ziaur Medical College Hospital, Bogura. A total 100 patients of peritonitis due to non-traumatic gastro-intestinal tract perforation were taken for study. Sample were collected by Convenience (purposive) sampling method. Midline incision and Para median incisions were performed as per standard technique. The details of operations, post-operative complications and follow up to be recorded and analyzed. Results: Opening time and closing time in midline incision is significantly less than paramedian (P <0.001). Incidence of wound infection and incidence of wound dehiscence in our study in midline group was less compared to paramedian group buy it is not significant. All forms of dehiscence ranging from superficial dehiscence to burst abdomen were included. Incidence of incisional hernia was significantly higher in midline incision (P<0.05). Healing time was significantly lower in midline compared to Paramedian group (P<0.05). Conclusion: It is concluded that midline incision is preferred compared to paramedian incision. Incidence of wound dehiscence and wound infection is less in midline incision. Medicine Today 2023 Vol.36 (1): 45-49